Using Virtual Reality (VR) Based on Constructivist Learning Theory to Enhance Engagement in Malaysian General Studies (MPU) Subjects - Mohammed Yasin, Nazreena; Ahmad faris Naqiyuddin Mohd Ghazi; Hanisah Md. Idris; Amir Faizal Abdul Hanif (Advances in Humanities and Contemporary Studies, 2025)
General studies subjects such as Malaysian Studies, Ethics and Civilization, Moral Studies and Integrity and Anti-Corruption Course are often perceived by students as secondary or peripheral compared to their core academic disciplines. This perception can lead to reduced motivation, superficial learning and limited engagement. This paper proposes the innovative integration of Virtual Reality (VR) technology, grounded in constructivist learning theory as a transformative pedagogical tool to address these challenges. Constructivist theory emphasizes active and experiential learning where students construct knowledge through exploration and interaction, making VR an ideal medium to enhance this process. By creating immersive and interactive experiences that simulate real-world historical events, cultural practices and ethical dilemmas, VR enables students to connect theoretical content with tangible experiences. Such an approach not only fosters deeper understanding and critical thinking but also encourages emotional and cognitive engagement. Moreover, this strategy aims to modernize the general studies curriculum by aligning it with contemporary digital trends and student learning preferences. Ultimately, the use of VR in Malaysian general studies (MPU) subjects has the potential to revitalize student interest, cultivate civic consciousness and promote lifelong learning in a dynamic and meaningful way. In addition, this paper highlights the practical implications for educators and curriculum designers while addressing challenges such as cost, infrastructure and the need for educator training to ensure sustainable adoption of VR in MPU subjects.